Metal attenuating therapies in neurodegenerative disease. (December 2011) - Mot, Alexandra I; Wedd, Anthony G; Sinclair, Layla; Brown, David R; Collins, Steven J; Brazier, Marcus W
The clinical and pathological spectrum of neurodegenerative diseases is diverse, although common to many of these disorders is the accumulation of misfolded proteins, with oxidative stress thought to be an important contributing mechanism to neuronal damage. As a corollary, transition metal ion dyshomeostasis appears to play a key pathogenic role in a number of these maladies, including the most common of neurodegenerative diseases. In this review, studies spanning a wide variety of neurodegenerative disorders are presented with their involvement of transition metals compared and contrasted, including more detailed treatise in relation to Alzheimer''s disease, Parkinson''s disease and prion diseases. For each of these diseases, a discussion of the evolving scientific rationale for the development of therapies aimed at ameliorating the detrimental effects of transition metal dysregulation, including results from various human trials, is then provided.